Morphometric evaluation and quantification using Fiji - Mathangasinghe, Yasith (Sri Lanka Anatomy Journal, 2021)
Fiji is a free software which can be used for image analysis in anatomical studies which allows obtaining accurate measurements of fine structures for morphometric evaluation. Fiji has a user-friendly interface with no requirement of programming skills, hence it has gained a wide interest among basic scientists. Here, we describe a protocol for obtaining basic measurements in gross anatomical and radiological studies using Fiji.
Keywords: Fiji; ImageJ; quantification; measurements